The interaction between a genetic variant in the NQO1 gene and environmental influences involving coenzyme Q10 has a significant impact on sperm motility - Batiha, Osamah; Hamzeh, Dina; A. Alfaqih, Mahmoud; Nawafleh, Mothanna; Khanjar, Hala; Al-zoubi, Esra’a (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Asthenozoospermia is a condition characterized by reduced sperm motility. Oxidative stress is known to impact sperm parameters, but Coenzyme Q10 (CoQ10), as an antioxidant, protects sperm from such damage. CoQ10 antioxidant activity requires reduction by the NAD(P) oxidoreductase 1(NQO1) enzyme. This study investigated the association between CoQ10 levels in seminal plasma, the NQO1P187S variant of the NQO1 gene, and asthenozoospermia risk. Research Design and Methods: A case-control study that included 127 asthenozoospermic patients and 55 normozoospermic controls was employed. Levels of CoQ10 in seminal plasma were measured using high-performance liquid chromatography (HPLC). The amplification refractory mutation system (ARMS)-PCR was used to detect the NQO1P187S polymorphism. Results: Asthenozoospemic patients had significantly lower levels of CoQ10 compared to normozoospermic controls (P=0.02). Additionally, asthenozoospermic patients with the CT/TT genotypes had lower levels of CoQ10 than controls carrying the same genotypes of the NQO1P187S variant. Regression analysis showed that CT/TT genotype was associated with an 8-fold increase in asthenozoospermia risk (OR=8.57, 95%CI: 2.09-3517, P=.003). Furthermore, a 1-unit increase in CoQ10 levels in participants with the CT/TT genotype was associated with a 3% reduction in asthenozoospermia risk. Conclusion: This study is the first in Jordan to provide evidence that an association between asthenozoospermia and CoQ10 levels in seminal plasma is influenced by the genetic background. CoQ10 protective role is affected by genetic variations of the NQO1P187S. This finding highlights an interaction between genetic and environmental factors in determining the risk of asthenozoospermia.